Physics for cambridge international AS & A level coursebook - Sang, David (New York ; Cambridge University Press, 2020)
Extensive research through lesson observations, teacher interviews and work with our online research community (the Cambridge Panel) means that this print and digital coursebook meets the real teaching needs of the physics classroom. Multi-part exam-style questions ensure students feel confident approaching assessment. New features provide reflection opportunities and self-evaluation checklists develop responsible learners. The coursebook provides a range of enquiry questions such as practical activities, group work and debate questions that develop 21st century skills.
AS & A level
Keywords: Text Book